Emotions affect learning about climate change - a case study of FFF - Deisenrieder, Veronika; Oberauer, Karin; Kubisch, Susanne; Parth, Sandra; Stötter, Hans; Keller, Lars (International research in geographical and environmental education, 2025)
Although the relevance of emotions for motivating climate change action is acknowledged in research, it lacks recommendation how to include emotions in Climate Change Education (CCE). This study draws on selected theories of emotions (the control-value theory according to Schutz and Pekrun ( 2007 ) and the wheel of emotions according to Plutchik ( 2001 )) and applies them in a CCE context. It then discusses emotions and their antecedents (value and control appraisals) experienced by secondary school students (N = 297) participating simultaneously in the Austrian CCE program k.i.d.Z.21 and in Fridays For Future (FFF) during the 2019/2020 school year. Results of quantitative and qualitative analyses indicate that FFF participants differ from other students (OS) in their emotions and their value and control appraisals. Characteristic findings are their predominant attribution of internal control (74.6%) and their extrinsic values (68.7%), as well as a high proportion of positive emotions (79%) compared to negative emotions (21%). For learning in CCE, the selected theories of emotions are recommended, as they provide a nuanced picture of the dominant emotions and their value and control appraisals within learners.